2009
DOI: 10.1158/1078-0432.ccr-08-3226
|View full text |Cite
|
Sign up to set email alerts
|

MMP11: A Novel Target Antigen for Cancer Immunotherapy

Abstract: Purpose: Matrix metalloproteinases (MMP) are zinc-dependent endopeptidases that mediate numerous physiologic and pathologic processes, including matrix degradation, tissue remodeling, inflammation, and tumor metastasis.To develop a vaccine targeting stromal antigens expressed by cancer-associated fibroblasts, we focused on MMP11 (or stromelysin 3). MMP11expression correlates with aggressive profile and invasiveness of different types of carcinoma. Experimental Design: To show the efficacy of a vaccine targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 35 publications
4
56
1
Order By: Relevance
“…Several genes that contribute to extracellular matrix remodeling, including Mmp10, Mmp3, Fbln, Krt7, and Muc1, can contribute to increased tumor invasion. Aberration to cell cycle regulators, such as the S100s, can cause unchecked growth, and changes to the regulation of cell signaling components Ret, Stat5a, Fzd10, Cxcl1, and Wif1 can lead to uncontrolled growth and differentiation (24,(34)(35)(36)(37). The abnormal response of these genes to E2 stimulation as a result of BPA treatment in utero is a particularly interesting link to the development of estrogen-sensitive cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes that contribute to extracellular matrix remodeling, including Mmp10, Mmp3, Fbln, Krt7, and Muc1, can contribute to increased tumor invasion. Aberration to cell cycle regulators, such as the S100s, can cause unchecked growth, and changes to the regulation of cell signaling components Ret, Stat5a, Fzd10, Cxcl1, and Wif1 can lead to uncontrolled growth and differentiation (24,(34)(35)(36)(37). The abnormal response of these genes to E2 stimulation as a result of BPA treatment in utero is a particularly interesting link to the development of estrogen-sensitive cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MMP II is expressed in 71% of esophageal cancer and may be an early event in esophageal tumorigenesis (18). Its expression in colorectal cancer (CRC) is associated with females, distal locations, infiltrative growth patterns and microsatellite stability of the patients (19,20), and even represents a novel expressed tumor associated antigen as the target candidate for CRC immunotherapy (21).…”
Section: Discussionmentioning
confidence: 99%
“…3B). Further RT-PCR analyses revealed that the expression of matrix metalloproteinases MMP10, MMP11, and MMP14, which reportedly facilitate cancer cell invasion (17)(18)(19), was enhanced in PHD3kd tumor cells (Fig. 3C).…”
Section: Inhibition Of Phd3 Enhances Tumorigenicity In Vitromentioning
confidence: 96%